Individuals with sickle cell hemoglobin have a high potential risk of COVID-19 - Bindhani, Basanta Kumar (Journal of Medical Biomedical and Applied Sciences, 2022)
The present article highlights the potential risk of COVID-19 among people with sickle cell genes. The current world is now fighting a pandemic situation due to the COVID-19. In December 2020, a new COVID-19 strain was identified in Britain, and it is 70% more transmissible than the previous strain. However, suppose the sickle cell carriers are affected by this virus. In that case, a severe and lethal condition will arise as people with sickle cell genes are associated with many comorbidities.